Soft Contact Manipulation of a Rigid Object Using Multibond Graph - Rathee, Rahul; Narwal, Anil Kumar; Vaz, Anand (Computer Assisted Methods in Engineering and Science, 2021)
Dexterous manipulation of a rigid object using artificial soft fingers is not easy to achieve. Instantaneous contact areas and the distribution of contact forces at the interfaces change dynamically during the soft contact manipulation of the object. A bond graph model for dynamics of the soft contact manipulation of a rigid object using two soft pads is developed. A cylindrical disc is used as the rigid object to be manipulated between two soft silicon rubber pads considered in place of soft fingertips, one above and the other below. The disc is grasped and rolled between the two pads so its center follows a desired horizontal displacement trajectory. A closed-loop feedback control system generates the required force to grasp and control the instantaneous position of the disc’s center. The model determines the instantaneous contact forces required for the desired manipulation. Simulation results validate the model.